(untitled) (Global Journal of Medical Research, 2020)
This presentation, based on various studies and our experiences, aims to highlight the paraprothetic and prosthetic protocol in oral implantlogy. The purpose of this paper is to perform prosthetic simulation prior to any surgical-implant procedure, as oral implant logy arises as a consequence and in response to prosthetics in cases of partial or total insufficiency. By comparing the clinical efficacy of the early and late protocol of dental implant placement according to the protocol. The objectives of this paper are to determine the position, diameter, and number of implants determined by the therapeutic angle that present cases with insufficiency and then indicate the need for prosthetic (suprastructural) work depending on the anatomical considerations of the jaw. Planned prosthetic work may have to vary depending on the appropriate jaw implant position. What needs to be emphasized is proper diagnosis and prosthetic treatment / planning as well as surgical stages.